El arte de caballete como expresión artística contemporánea en la Casa de la Cultura Ecuatoriana Dr. Benjamín Carrión Núcleo de El Oro, en los años 2012 - 2013. - Toro Feijoó, Francisco Xavier (2015)
At present the Art in Ecuador, covers the evolution of architecture, painting and sculpture Ecuador, trying to give a historical approach to its development and current from the nineteenth century to today. In the province there is a contemporary art form that facilitates a new relationship between culture and society and has a better concept of what is contemporary art, people know what an easel aside new artistic trend is. In the city of Machala a shortage of places that promote the dissemination of art and culture as means of cognitive development is evident, which the implementation of a proposal that meets the social need for Contemporary Art events is necessary.